1992
DOI: 10.1007/bf00195664
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of conditions for the culture of somatic embryos of white spruce for improved triacylglycerol biosynthesis and desiccation tolerance

Abstract: In order to enhance post-germinative vigour, somatic embryos of Picea glauca (Moench) Voss. were matured under in-vitro conditions that stimulated triacylglycerol (TAG) biosynthesis. In P. glauca seeds over 90% of the TAG was stored within the megagametophyte, and isolated zygotic embryos contained twice the amount of TAG of somatic embryos cultured for four weeks on basal medium containing 16 μM abscisic acid (ABA). Polyethylene glycol-4000 (PEG) as a non-permeating osmoticum with ABA promoted TAG biosynthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(71 citation statements)
references
References 28 publications
3
68
0
Order By: Relevance
“…Several authors have suggested that the role of ABA in somatic embryogenesis is the inhibition of cleavage polyembryony with consequent development of individual somatic embryos Boulay et al, 1988;Krogstrup et al, 1988;, to stimulate the accumulation of nutrients, lipids, proteins, and carbohydrates , and to suppress precocious germination (Roberts et al, 1990). The addition of PEG induces water stress similar to that generated by desiccation (Attree and Fowke, 1993), increases storage product deposition (Attree et al, 1992;Misra et al, 1993) and tolerance to water loss (Attree et al, 1991). However, some authors have reported that PEG promotes maturation but inhibits further development of Picea glauca (Kong and Yeung,1995) and P, abies somatic embryos (Bozhkov and von Arnold, 1998).…”
Section: Maturation Of Somatic Embryosmentioning
confidence: 99%
“…Several authors have suggested that the role of ABA in somatic embryogenesis is the inhibition of cleavage polyembryony with consequent development of individual somatic embryos Boulay et al, 1988;Krogstrup et al, 1988;, to stimulate the accumulation of nutrients, lipids, proteins, and carbohydrates , and to suppress precocious germination (Roberts et al, 1990). The addition of PEG induces water stress similar to that generated by desiccation (Attree and Fowke, 1993), increases storage product deposition (Attree et al, 1992;Misra et al, 1993) and tolerance to water loss (Attree et al, 1991). However, some authors have reported that PEG promotes maturation but inhibits further development of Picea glauca (Kong and Yeung,1995) and P, abies somatic embryos (Bozhkov and von Arnold, 1998).…”
Section: Maturation Of Somatic Embryosmentioning
confidence: 99%
“…The levels of TAGs in somatic embryos of Picea glauca also increased nine fold, in response to the addition of (+)-ABA (Attree et al, 1992). Developing wheat embryos (Triticum aestivum L.) showed a 55% TAG increase in response to supplementation with ABA or high osmoticum (400 mM mannitol) (Rodriguez-Sotres and Black 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Abscisic acid (ABA) in particular, is a plant hormone involved in many physiological responses including mediation of lipid accumulation in developing seeds (Wilen et al, 1990;Walker-Simmons et al, 1994;Sholi et al, 2009). These effects extend to related developing embryos and cell cultures (Browse et al, 1986;Finkelstein and Somerville 1989;Wilen et al, 1990;Holbrook et al, 1991;Attree et al, 1992;Holbrook et al,1992;Weselake et al, 1998;Weselake 2000;Davoren et al, 2002). For example, zygotic embryos of Brassica napus L. cv.…”
Section: Introductionmentioning
confidence: 99%
“…ABA inhibits cleavage polyembryony, thus allowing embryo singulation, further development, and maturation. Furthermore, ABA is involved in the accumulation of storage proteins (Dunstan et al, 1998), celular expansion control (Gutmann et al, 1996) and triacylglycerol biosynthesis (Attree et al, 1992). The effectiveness of the ABA treatment may be enhanced by an increase in the osmotic level of the culture medium by the addition of hexose sugars, sugar alcohols, or neutral polymers such as polyethylene glycol (Bonga et al, 1995).…”
Section: Introductionmentioning
confidence: 99%